The Chair’s Role: Faculty, Mentor, Colleague, Supervisor? - Mary Elizabeth Zimmer; Richard Scott Cohen (Academic Chairpersons Conference Proceedings, 2019)
The day a faculty assumes the role of Chair, his or her role has changed. Once a colleague and friend to fellow faculty, now becomes the supervisor and mentor. Juggling these roles can be difficult and changes with each individual relationship. The new Chair can lose friendships and can become isolated. This session will discuss the many roles that the Chair has and how we cope with the changing role of Chair.
Keywords: mentor; colleague; supervisor; relationships